SYNTHESIZE OF GEL POLYMER ELECTROLYTES FOR HIGH CONDUCTIVITY AND GOOD CYCLIC VOLTAMMETRY - V., Sethuprakhash; Rajaa Shaari, Hafizah; A., Shah; Nallaluthan, Kesevan (International Journal of Psychosocial Rehabilitation, 2020)
Ionic conductivity for gel polymer electrolytes (GPE) is obtained, and the polymers are used in zinc-air and tin-air battery applications. The gel polymer consists of methanesulfonic acid (MSA) as additives and polyacrylamide (PAAm) as host polymer. The objective of this work is to synthesize one GPE which gives high conductivity and good cyclic voltammetry The PAAm-MSA gel electrolytes were prepared with different concentration of MSA. The chemical interaction between PAAm and MSA was studied by FTIR. The impedance spectroscopy technique has been employed to compare the ionic conductivity of these polymer electrolytes. The ionic conductivity of the PAAm ( 10-2 S/cm) electrolyte increases by an order of magnitude to 10-1 S/cm. It was observed that when 3.0 M of MSA is added into the host hydrogel polymer, the ionic conductivity is enhanced from 4.9 × 10-2 S/cm to 7.1 × 10-1 S/cm. The best GPE synthesized in this work is 3.6M PAAm-MSA.